Bibliometría De Psicología Política En Colombia Entre Los Años 2005 Al 2017 (2019)
The main objective of this study is to identify the written production on political psychology in Colombia from 2005 to 2017, a collection of articles on political psychology is carried out in Colombia through the review of electronic journals of Colombian universities, resulting in 21 magazines in which 10 were found, the magazines with publications are: Psychologica Deeds El Caribe, Universitas Psychologica, Diversities Perspectives End Psychologica, Testis Psychologica, Revisit Cues Psychologica, Psychologica Advances De La Discipline, Psychologica Advances De La Discipline, Revisit Dialog De Sabers, Revisit Faulted Nacional De Salad Publican.